Proses Pemecahan Masalah Matematika Kontekstual Open-Ended Peserta Didik SMP Ditinjau Dari Tipe Kepribadian - Haulainy, Dewi Rahmah; Kurniasari, Ika (MATHEdunesa, 2024)
Every student has a different mathematical problem solving process because there are several factors that influence, one of which is personality type. The aims of the research to describe the process of junior high school students in terms of personality type in solving contextual open-ended mathematical problem. The methode of this research is qualitative with the characteristic subjects are personality type sanguine, melancholy, choleric, and phlegmatic. The instrument consisted of personality type questionnaires, test, and interviews. The results showed that at the step of understanding the problem, student with a choleric personality type are less fluent and detailed in explaining the known and asked information. While student with phlegmatic personality type did not write down the known and asked information on the answer sheet at all due to difficulties when converting the information to mathematical form. All four personality types mention the adequacy of information by looking at what is known and asked information. At the step of devising a plan, students with sanguine, melancholy, and phlegmatic personality types explain three stages in detail while student with choleric personality types only explain two stages. At the step of carrying out the plan, student with melancholy personality type can write down more possibilities than other personality types. At the step of looking back, students with sanguine, melancholy, and phlegmatic personality types rechecked the answer by recalculating, while student with choleric personality type did not do that. The four personality types explain conclusions using their own language well but in writing conclusions, student with melancholy personality type do not write them on the answer sheet.